2003
DOI: 10.1029/2003jd003843
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of microwave absorption models and retrievals of cloud liquid water using clear‐sky data

Abstract: [1] Passive microwave radiometers have a long history in the remote sensing of atmospheric liquid and water vapor. Retrievals of these quantities are sensitive to variations in pressure and temperature of the liquid and water vapor. Rather than use a statistical or climatological approach to account for the natural variability in atmospheric pressure and temperature, additional information on the atmospheric profile at the time of the radiometer measurements can be directly incorporated into the retrieval proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 20 publications
4
70
0
Order By: Relevance
“…Although there are 5-years of data used per month, these distributions should be regarded as rough estimates of the month-to-month differences in LWP. This is because recent research has found that MWR uncertainties exist in the LWP retrievals that limit the attainable accuracy to between 20-30 g m À2 [Liljegren and Lesht, 1996;Westwater et al, 2001;Marchand et al, 2003;Turner et al, 2007], which represents a large uncertainty compared to many of the values shown. Still the shift shown, from smaller to larger LWP from March through June, is consistent with climatological considerations that optically thinner stratiform cloud tend to occur in spring versus summer [e.g., Leontyeva and Stamnes, 1994].…”
mentioning
confidence: 99%
“…Although there are 5-years of data used per month, these distributions should be regarded as rough estimates of the month-to-month differences in LWP. This is because recent research has found that MWR uncertainties exist in the LWP retrievals that limit the attainable accuracy to between 20-30 g m À2 [Liljegren and Lesht, 1996;Westwater et al, 2001;Marchand et al, 2003;Turner et al, 2007], which represents a large uncertainty compared to many of the values shown. Still the shift shown, from smaller to larger LWP from March through June, is consistent with climatological considerations that optically thinner stratiform cloud tend to occur in spring versus summer [e.g., Leontyeva and Stamnes, 1994].…”
mentioning
confidence: 99%
“…Since the accuracy of the absorption model dramatically influences the radiative transfer modeling results, many studies inter compared different absorption models [57,[60][61][62][63]. Such intercomparison is usually fulfilled for the downwelling radiation to minimize the errors associated with inaccurate estimation of the ocean constituent of the radiation.…”
Section: Atmospheric Absorption Modelmentioning
confidence: 99%
“…To stabilize the temperature of the receiver components, the packaging technique described in [1] was employed, consisting of an insulated cold-plate in a box, in a temperature controlled enclosure. The resulting component plate temperature stability limited the effect of receiver-gain rate-of-change to below 100 K/Hr, requiring system gain and offset calibrations only a few times a minute to achieve a sub-K measurement precision.…”
Section: Of 29mentioning
confidence: 99%
“…Several recent advances however make the development of a 183 GHz radiometer more practical today. These include the commercial availability of subharmonically 3 OF 29 pumped Schottky mixers and conical feed horns, and an ultra stable radiometer design developed at K-band by Tanner [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation